Synthesis and Discovery of Schiff Base Bearing Furopyrimidinone for Selective Recognition of Zn2+ and its Applications in Cell Imaging and Detection of Cu2+ - Hu, Yanggen; Luo, Chao; Gui, Lili; Lu, Jing; Fu, Juncai; Han, Xinya; Ma, Junkai; Luo, Lun (Frontiers in Chemistry, 2021)
A simplefuro[2,3-d]pyrimidinone-based schiff base FPS was synthesized via aza-Wittig reaction and structure elucidation was carried out by spectroscopic studies FT-IR, 1H NMR and 13C NMR and mass spectrometry. FPS showed weak fluorescence emission in methanol and the selectivity of FPS to different metal ions (Mn2+, Ca2+, Fe2+, Fe3+, Mg2+, Al3+, Ba2+, Ag+, Co2+, Na+, K+, Cu2+, Zn2+, Pb2+, Bi3+) were studied by absorption and fluorescence titration. The results show that FPS has selective fluorescence sensing behavior for Zn2+ ions and the limit of detection (LOD) was calculated to be 1.19×10-8mol/L. Moreover, FPS-Zn2+ acts as a metal based highly selective and sensitive new chemosensor for Cu2+ ions and the limit of detection (LOD) was calculated to be 2.25×10-7 mol/L. In accordance with the results and theoretical calculations, we suspected that the binding mechanism of FPS to Zn2+ and Cu2+ were assigned to be the cooperative interaction of Zn2+(Cu2+)-N.